Pengaruh Media Powerpoint Interaktif dalam Pembelajaran Sains Berbasis Proyek Terhadap Kemampuan Berpikir Kreatif Siswa SD - Ricke Leosita Utami; Endang Widi Winarni; Irwan Koto (UNIB Press, 2024)
The aim of the research is to analyze the influence of interactive PowerPoint media in project-based science learning on the dimensions of the ability to think fluently, think flexibly, think original and the relationship between the ability to think fluently, flexibly and original in project-based science learning with interactive PowerPoint media. The type of research is quasi-experimental research using a pretest-posttest control group design. The instruments used are question instruments and expert validation sheets. Based on the Asymp sig value. 2 tailed is 0.000 < 0.05. It can be concluded that there is a significant influence of the use of interactive PowerPoint media in project-based science learning on the dimensions of the ability to think fluently, flexibly and originally. then the sig value is obtained. (2-tailed) sperman rank correlation. 0.05. It can be concluded that there is no relationship between the dimensions of the ability to think fluency, flexicibility and originality using PowerPoint media in project-based science learning.